Transcriptome analysis of the effect of GA(3) in sugarcane culm - Chandra, A. (3 Biotech, 2019)
Our earlier studies have indicated that GA(3), being a growth hormone, increases internodal length, in turn increasing sink strength and improving sucrose accumulation in sugarcane. In this study, transcriptomic level analysis was carried out on internodal samples of a high sugar accumulating variety (CoLk 94184) of sugarcane, to determine the effect of exogenous application of GA(3) vis a vis functional analysis of differentially expressing transcripts. Overall, a total of 201,184 transcripts were identified, with median contig length of 450 bp and N50 length of 1029 bp. Analyzing the data from control and GA(3)-treated canes, at 0.01 significance, a total of 1516 differentially expressing transcripts were identified in bottom internodes and 1589 in top internodes. A KEGG (enrichment) analysis grouped the transcripts into 153 plant-related functional categories. From among these, the transcripts which were functionally relevant to sugar metabolism and photosynthesis were sieved out. Starch and sucrose metabolizing genes showed maximum fold change of 5.0 and 3.0 among top and bottom internodal samples. A homology match using Blastx analysis tool yielded 65 transcripts/differentially expressed genes (DEGs) which were found to share homology with C(4) plants like Saccharum, Sorghum and Zea mays. Differentially expressing transcripts from both top and bottom internodes were validated by qRT-PCR, indicating their importance in such study. Results also enriched sugarcane transcriptome resources useful for omics study in genus Saccharum and family Poaceae. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13205-019-1908-0) contains supplementary material, which is available to authorized users.